Data Analysis And Design Of Data Based On The Database Of The Dprd Members Of The Regency Of Batu Bara DPRD - Mahbub Elby, Muhammad Khairil; Gunawan, Andri; Dhani Alfarhabi, Ikhwan (Journal of Computer Science and Informatics Engineering, 2022)
The DPRD Secretariat has a problem related to archiving the personal data of the Batu Bara DPRD Members, which is sometimes difficult to access. This is because the Batu Bara DPRD secretariat still archives all DPRD member data in computer storage which is sometimes lost or even damaged due to viruses, device damage and so on, besides that data cannot be accessed from other places because it is left on the DPRD secretariat PC. The purpose of this study was to analyze and design a prototype of the Database-based Personal Data Information System for Members of DPRD Batu Bara Regency, with the HMVC (Hierarchical Model View Control) architectural method on MySQL PHPMyAdmin as the DBSM which is expected to help facilitate the creation of a database that is compatible as needed. . So that it can minimize the loss or damage of personal data for members of the Batu Bara Regency DPRD, besides that it can also be accessed anywhere without having to open the archive on the DPRD Secretariat PC. Keywords: Analysis, Design, PHPMyAdmin, HMVC, DPRD Archives.